Spatial Ability of Junior High School Students in Solving Open-Ended Questions Viewed from Mathematical Anxiety - Ramadhani, Risqia (Journal of the Indonesian Mathematics Education Society, 2024)
The aim of this research is to identify and describe the spatialabilities of students with high, medium and low mathematics anxiety in solving open ended problems. The research methodology employed in this study isqualitative, and the research design is descriptive. The conclusion shows that students with low mathematics anxiety can solve the questions that have been given and meet the indicators of spatial ability when compared with students who have moderate and high mathematics anxiety who cannot solve the questions and therefore do not meet the indicators of spatial ability.